EFSUMB Guidelines and Recommendations on the Clinical Use of Ultrasound Elastography. Part 1: Basic Principles and Technology - Bamber, J.; Cosgrove, D.; Dietrich, C. F.; Fromageau, J.; Bojunga, J.; Calliada, F.; Cantisani, V.; Correas, J.-M.; D’Onofrio, M.; Drakonaki, E. E.; Fink, M.; Friedrich-Rust, M.; Gilja, O. H.; Havre, R. F.; Jenssen, C.; Klauser, A. S.; Ohlinger, R.; Saftoiu, A.; Schaefer, F.; Sporea, I.; Piscaglia, F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
The technical part of these Guidelines and Recommendations, produced under the auspices of EFSUMB, provides an introduction to the physical principles and technology on which all forms of current commercially available ultrasound elastography are based. A difference in shear modulus is the common underlying physical mechanism that provides tissue contrast in all elastograms. The relationship between the alternative technologies is considered in terms of the method used to take advantage of this. The practical advantages and disadvantages associated with each of the techniques are described, and guidance is provided on optimisation of scanning technique, image display, image interpretation and some of the known image artefacts.
Keywords: elastography; elasticity; radiation force; shear wave; stiffness; shear modulus; strain; transient; ultrasonography